2014
DOI: 10.3892/mmr.2014.2854
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-96 promotes the proliferation of colorectal cancer cells and targets tumor protein p53 inducible nuclear protein 1, forkhead box protein O1 (FOXO1) and FOXO3a

Abstract: Abstract. MicroRNAs (miRNAs) are a conserved class of small, endogenous, non protein-coding RNA molecules that are capable of regulating gene expression at post-transcriptional levels and are involved in diverse cellular processes, including cancer pathogenesis. It has previously been reported that miRNA-96 (miR-96) is overexpressed in human colorectal cancer (CRC). However, the underlying mechanism of miR-96 regulation in CRC remains to be elucidated. In the present study, miR-96 was confirmed to be upregulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
39
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(45 citation statements)
references
References 31 publications
1
39
0
Order By: Relevance
“…Targetscan prediction revealed three members of the FOXO protein family, including FOXO1, FOXO3 and FOXO4 as potential targets of the miR-183-96-182 cluster. However, only FOXO1 and FOXO3 have been confirmed by previous studies [16, 35, 49, 6165], in various types of cancers such as, prostate [63, 66, 67], bladder [43, 68], colorectal [62], breast [69], lung [61], lymphoma [64], and endometrial carcinoma [70] (Table 1). Additionally, recent studies have indicated that miR-182 promotes cell proliferation and tumor invasion by targeting FOXF2 [71, 72], a known inhibitor of MMPs and WNT5A [73, 74].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Targetscan prediction revealed three members of the FOXO protein family, including FOXO1, FOXO3 and FOXO4 as potential targets of the miR-183-96-182 cluster. However, only FOXO1 and FOXO3 have been confirmed by previous studies [16, 35, 49, 6165], in various types of cancers such as, prostate [63, 66, 67], bladder [43, 68], colorectal [62], breast [69], lung [61], lymphoma [64], and endometrial carcinoma [70] (Table 1). Additionally, recent studies have indicated that miR-182 promotes cell proliferation and tumor invasion by targeting FOXF2 [71, 72], a known inhibitor of MMPs and WNT5A [73, 74].…”
Section: Resultsmentioning
confidence: 77%
“…Notably, miR-96 has also been found to inhibit the TSG RECK [40, 83, 84] and EFNA5 [85]. Besides, miR-96 and miR-182 were found to have an inhibitory effect on TP53INP1 expression [62, 86]. Collectively, the available evidence indicates that miR-183-96-182 cluster could promote cell proliferation in various cancer types (Table 1).…”
Section: Resultsmentioning
confidence: 99%
“…At this threshold, in addition to rs2382817, 11 IBD risk SNPs were associated with CRC risk (Table 1), of which five were positively associated with CRC risk, whereas the other seven displayed an inverse relationship. A number of these SNPs annotate genes with documented roles that are relevant to CRC development, such as Wnt-signalling [ WNT4 , (17)], tumour suppression [ MAPKAPK5 , FOXO1 (18,19)] and cellular transformation [ CDC42 , CEBPB (20,21)] (Table 1). We examined for an association between the genotype of these 12 SNPs and the molecular subtype of CRC, and found no evidence of a relationship (Supplementary Material, Table S3).…”
Section: Resultsmentioning
confidence: 99%
“…A single miRNA might regulate several target mRNAs due to the relatively short seed region. For instance, FOXO1 and FOXO3a are both direct targets of miR-96 in colorectal cancer and HCC [71, 75]. Meanwhile, FOXO3 and FOXO1 are found to be critical targets of miR-9 in hematopoietic cells [76].…”
Section: Fox-related Mirnasmentioning
confidence: 99%